Obtaining Optimum Peel Color of Fresh Florida Citrus - Mark A. Ritenour; Fernando Alferez (EDIS, 2020)
This article informs about pre- and postharvest factors influencing citrus fruit peel color for fresh markets and the best postharvest treatment methods for obtaining excellent peel color.